Metamorfoses. Ensaio de projeto para um edifício de habitação plurifamiliar - Luís Miguel Sampaio Araújo (2020)
This dissertation assumes itself as a personal journal of reflections around research that informs the process of an architectural proposal. The entire process depicts a workflow where the bibliographic sources brief the design decisions, and these guide the search process itself. From this set, an essay for a residential building is born, at Vila do Conde, which seeks to be the catalyst for a new transformation.